The Value of Unfashionable Fashion. The Management and Evaluation of Unsold Goods according to Fashion Cycle and Circular Economy - Fabbri, Luca (ZoneModa Journal, 2021)
The fashion system has very often worked without taking very much attention to unsold goods and not used raw materials. The product life cycle is usually very short and products lose their value very fast as every season fashion is forward-looking. Discount shops and outlets are the final step where the past seasonal collections are on sale but sometimes it can happen that goods are destroyed in order not to damage the brand value and exclusivity. This behaviour is not very sustainable anymore. Nowadays this situation is changing and a new approach to this issue is arising. Brands have understood how important brand heritage is and they have started to collect and preserve their past. For many companies recycling and upcycling strategies are becoming more and more common and they offer this new product proposal to the market as a new trend to preserve our planet. On the other side, consumers are changing their shopping and consumption habits. Second-hand shops and websites like Vestiare Collective seem to be the evidence that a new culture and way of thinking is arriving.